PARASITIC SKIN INJURIES IN DONKEYS EQUUS ASINUS FROM CHORONI, ARAGUA STATE, VENEZUELA - Morales B, Abelardo A. (2010)
Three donkeys (Equus asinus Linnaeus, 1758), two males and a female sex, between 5-8 years of old, inathletic shape, in Choroni, Aragua, Venezuela were examined. Clinical examination evidenced hirsute hair and moderate body condition. Nodular dermatitis like skin lesions showed crusted erythematous to chronic ulcerated center with edges of reepithelialization complicated. Tissue sections were taken from skin in affected area described above, by excision biopsy technique. The samples were fixed in 10% formalin and processed by conventional histological processing and stained with hematoxylin and eosin. Additional special stains used included PAS, Giemsa and Grocott. The histological section showed nodular erosive ulcerative crusting dermatitis. Perivascular dermatitis type I and inflammatory infiltrate were observed. Mononuclear lymphocytes and polymorphonuclear neutrophilic plasmocytorious infiltrate were abundant along with reactive macrophages. The special stains PAS, Giemsa and Grocott showed amastigotes forms of flagellates, and abundant secondary bacteria and fungi. In conclusion, we report three cases of erythematous nodular dermatitis associated with chronic infection of Leishmania sp. reported in donkeys of Choroni, Aragua, Venezuela.